Antibiotic Resistant Pattern and Resistant Gene Identification of Staphylococcus aureus from Chicken Farm in Bogor - Hermana, Nabila Swarna Puspa; Afiff, Usamah; Safika, Safika; Indrawati, Agustin; Pasaribu, Fachriyan Hasmi (Jurnal Veteriner; Vol 22 No 2 (2021)DO - 10.19087/jveteriner.2021.22.2.262, 2021)
Chicken is one of the important protein source in Indonesia. Moreover, the largest population of chicken layer and poultry in Indonesia is known situated at West Java province with Bogor manicipality as the main producer. The aims of this study were to determine the antibiotic resistance pattern of Staphylococcus aureus isolated from poultry and layer farm in Bogor. The study also identified gene encoded the resistance. Cloacal swab samples were collected from chicken broiler and layer farm in Bogor manicipality. The samples were then cultured in Mannitol Salt Agar (MSA) medium to obtain S. aureus . Suspected colony was then confirmed by biochemical test. Positive strains were tested against several antibiotics and the diameter of clear zone arround of colony was interpreted based on Clinical and Laboratory Standard Institute. Furthermore, the DNA from resistant strains were then extracted, followed by detection of the resistance gene by using polymerase chain reaction (PCR) method. A total of 14 isolates of S. aureus were positive from poultry farm, and 15 isolates from layer farm. Most of all were resistant to tetracycline, ampicillin, oxytetracycline, erythromycin and nalidixic acid. On the other hands, several strains were sensitive to gentamycin and chloramphenicol. The study showed 28 isolates out of them were multi-drug resistant. Resistant gene such as blaTEM, gyrA and tetA were also identified in some isolates except for ErmB gene which was found in isolates originated from poultry farm. In conclussion, S. aureus in both farm showed mostly multi-drug resistant to several antibiotics which were supported by identification of resistant gene among isolates.